Patients' and nurses' preferences for autoinjectors for rheumatoid arthritis: results of a European survey - Tischer B; Mehl A (Patient Preference and Adherence, 2018)
Bernd Tischer,1 Andrea Mehl2 1Kantar Health GmbH, Munich, Germany; 2Sandoz International GmbH, Holzkirchen, Germany Purpose: This survey investigated patients’ and nurses’ preferences among four different autoinjectors used for subcutaneous delivery of medication for rheumatoid arthritis (RA). Methods: In a multinational survey in five countries, 200 patients with RA and 100 nurses training patients on the use of autoinjectors participated in face-to-face interviews. Respondents were asked to rate the importance of eleven autoinjector attributes and to compare the autoinjectors for etanercept (Enbrel®, MyClic® autoinjector), adalimumab (Humira®, Humira pen), and an etanercept biosimilar (Benepali®, Molly® autoinjector) with a demonstration autoinjector for a new etanercept biosimilar – Erelzi® (SensoReady® autoinjector). Results: Easy grip and ease of performing self-injection were the most important attributes identified by both groups. Overall, 79% of the patients rated the SensoReady autoinjector easier to use than their currently used injection device (86% of MyClic users, 84% of Humira pen users, and 63% of Molly users). In the patient survey, the SensoReady performed better than the other autoinjectors on the attributes visual feedback after completion of injection, easy to grip, and convenient shape. Nurses also rated the SensoReady easier to use than the MyClic (95%), Humira pen (97%), or Molly (91%). When asked which autoinjector they would recommend to a patient with RA who had not used an autoinjector before, 81% of patients and 90% of nurses selected the SensoReady. Conclusion: Both patients and nurses perceived the SensoReady to be easier to use compared with other available injection devices. The main reasons for this preference were the buttonless injection, 360° viewing window for feedback (visual confirmation of dose injection), and convenient triangular shape making the injection device easy to grip. Patients and nurses were most likely to recommend the SensoReady autoinjector over other autoinjectors to patients with RA. Keywords: SensoReady®, Erelzi® pen, easy grip, convenience, autoinjection-device test, etanercept biosimilar